Environmentally sustainable management practices support veterinary staff wellbeing - Scott, Danielle; Davis, Lyn; Duncan, Colleen (Frontiers in Veterinary Science, 2025)
Veterinary technicians and assistants are integral to the daily operations of veterinary practices and have the potential to serve as key advocates for sustainability within the profession. This study aimed to assess veterinary support staff perspectives on the health impacts of climate change on companion animals, their perceived professional responsibilities in addressing climate-related health issues, and the availability of relevant educational resources. An electronic survey was distributed to veterinary staff across the United States through veterinary practices, AVMA-accredited technician programs, and technician-focused social media platforms. Findings indicate that technicians, technician students, and assistants overwhelmingly acknowledge the occurrence of climate change and its relevance to animal health. Respondents expressed a strong belief that veterinary staff should be informed about the health implications of climate change, identified a substantial gap in education on this topic, and demonstrated support for implementing sustainable practices within clinical settings. These results underscore the urgent need to integrate climate-related health education into veterinary support staff curricula and highlight the potential for sustainable initiatives to contribute to improved staff engagement and retention.